Comparative laboratory effectiveness of low molecular weight heparins in patients with acute coronary syndrome and no ST segment elevation - R. M. Linchak; V. S. Popov; K. F. Kim (Кардиоваскулярная терапия и профилактика, 2011)
Aim. To compare anti-Xa plasma activity levels in patients with acute coronary syndrome (ACS) and no ST segment elevation (non-STE ACS), receiving enoxaparin, nadroparin, or dalteparin. Material and methods. In total, 90 patients with non-STE ACS were divided into three groups (n=30 in each group), by the type of low molecular weight heparin (LMWH) administered. All groups were comparable by age and gender structure, body mass index, and creatinine clearance levels. Anti-Xa activity was measured at admission and 6 hours after the first LMWH injection. Results. In all groups, anti-Xa activity was significantly increased at 6 hours after the first LMWH injection. At the end of the follow-up period, the change in this parameter was 0,73±0,11 IU/ml, with baseline level of 0,07±0,05 IU/ml, in the enoxaparin group. In the dalteparin group, the respective values were 0,52±0,12 and 0,05±0,03 IU/ ml, and in the nadroparin group, they were 0,61±0,10 and 0,06±0,05 IU/ml, respectively. The percentage of patients with achieved therapeutic anti-Xa activity (≥0,6 IU/ml) was maximal in the enoxaparin group (93%), being significantly higher than in the dalteparin and nadroparin groups (63% and 77%, respectively). Conclusion. Enoxaparin, dalteparin, and nadroparin therapy in non-STE ACS patients was associated with significantly increased plasma anti-Xa activity. However, the percentage of the patients with achieved therapeutic levels of anti-Xa activity was maximal in the enoxaparin group.